Effects of Six Months Training on Physical Capacity and Metaboreflex Activity in Patients with Multiple Sclerosis - Magnani, Sara; Olla, Sergio; Pau, Massimiliano; Palazzolo, Girolamo; Tocco, Filippo; Doneddu, Azzurra; Marcelli, Maura; Loi, Andrea; Corona, Federica; Corona, Francesco; Coghe, Giancarlo; Marrosu, Maria G.; et al. (Frontiers in Physiology, 2016)
Patients with multiple sclerosis (MS) have an increased systemic vascular resistance (SVR) response during the metaboreflex. It has been hypothesised that this is the consequence of a sedentary lifestyle secondary to MS. The purpose of this study was to discover whether a six-month training program could reverse this hemodynamic dysregulation. Patients were randomly assigned to one of the following two groups: the intervention group (MSIT, n= 11), who followed an adapted training program; and the control group (MSCTL, n= 10), who continued with their sedentary lifestyle. Cardiovascular response during the metaboreflex was evaluated using the post-exercise muscle ischemia (PEMI) method and during a control exercise recovery (CER) test. The difference in hemodynamic variables such as stroke volume (SV), cardiac output (CO) and SVR between the PEMI and the CER tests was calculated to assess the metaboreflex response. Moreover, physical capacity was measured during a cardiopulmonary test till exhaustion. All tests were repeated after 3 and 6 months (T3 and T6 respectively) from the beginning of the study. The main result was that the MSIT group substantially improved parameters related to physical capacity (+5.31±5.12 ml·min-1/kg in maximal oxygen uptake at T6) in comparison with the MSCTL group (-0.97±4.89 ml·min-1/kg at T6; group effect: p=0.0004). However, none of the hemodynamic variables changed in response to the metaboreflex activation. It was concluded that a six-month period of adapted physical training was unable to reverse the hemodynamic dys-regulation in response to metaboreflex activation in these patients.